Coordenador pedagógico e os condicionantes do ser e do vir a ser um formador - Camargo, Debora Rana de (2013)
This study builds on the realization that Pedagogical Coordinators of the Municipal Education System of São Paulo, are not necessarily acting as teacher educators. This study aims at analyzing the necessary conditions for the Pedagogical Coordinator to act as teacher educator, performing in-service training in Municipal schools. The aim of our research has been to analyze the Cadernos de Apoio e Aprendizagem (Learning and Support Workbooks) produced by the Bureau of Education of São Paulo in partnership with Fundação Padre Anchieta, which distribution in the municipal public system started in 2010. Such material aims at giving greater effect to Learning Outcomes by means of planning activities that, organized into teaching units, relate to these outcomes. The material is composed by the Teachers Workbook, the Students Workbook and a complementary Video. Four Pedagogical coordinators whose teachers work in the first years of Primary Education and make use of such Workbooks were subject of the present research. Data gathering was conducted through semi-structured interviews, with theme-based questions. Data analysis was conducted through the construction of double-entry data tables in which the columns contained thematic aspects of the interviews and the lines contained the interviewees answers. Data analysis and interpretation reveals that, although Pedagogical Coordinators are aware that teacher education and Education Bureau policy implementation are among their professional duties, these tend to be partly carried out, or not carried out at all on their daily performance. What prevents it from happening are conditions related to training issues, conjunctural, and structural policies that were here organized into categories of analysis and could, thus, be investigated in further detail. It was concluded that, even with the support of the Bureau of Education, with teaching materials and guarantee of one Pedagogical Coordinator per school, if the basic conditions are not met, the process of in-service training is not carried out. This happens either due to poor conditions provided by the Bureau of Education, or, to the State accountability for personal assignments, which are, therefore, not transferable